1989
DOI: 10.2134/agronj1989.00021962008100040024x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Five Food Legume Crops to an Irrigation Gradient Imposed During Reproductive Growth

Abstract: Food legumes, an excellent source of protein and soil fertility improvement, offer small farmers a means of intensifying cropping on rice lands in semiarid and tropical regions. Unfortunately food legume productivity is often limited by variation in the amount and distribution of rainfall. The study was conducted to compare differential responses of mungbean (Vigna radiata L.), soybean [Glycine max (L.) Merr.], cowpea [Vigna unguiculata (L.) Walp.], peanut (Arachis hypogaea L.), and pigeonpea (Cajanus cajan L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
1
15
1
Order By: Relevance
“…A similar lack of stability in guar yields was noted over an eight-year period at 16 locations throughout Oklahoma and Texas, with a large portion of the variability attributed to environment (Staff ord, 1982). Pod numbers and seeds per plant were also important to grain production by mung bean, cowpea, soybean, and pigeon pea, and were aff ected by availability of water (Senthong and Pandey, 1989). Pod numbers and seeds per plant were also important to grain production by mung bean, cowpea, soybean, and pigeon pea, and were aff ected by availability of water (Senthong and Pandey, 1989).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A similar lack of stability in guar yields was noted over an eight-year period at 16 locations throughout Oklahoma and Texas, with a large portion of the variability attributed to environment (Staff ord, 1982). Pod numbers and seeds per plant were also important to grain production by mung bean, cowpea, soybean, and pigeon pea, and were aff ected by availability of water (Senthong and Pandey, 1989). Pod numbers and seeds per plant were also important to grain production by mung bean, cowpea, soybean, and pigeon pea, and were aff ected by availability of water (Senthong and Pandey, 1989).…”
Section: Discussionmentioning
confidence: 64%
“…The costs of such products are volatile and currently increasing. Some were incorporated into cropping systems in regions of the tropics and subtropics to diversify agricultural production (Pandy et al, 1983;Senthong and Pandey, 1989;Mandal et al, 1990). There are many subtropical and tropical grain legumes that could be used as feedstock in the SGP.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of precipitation and temperature on yields of forage crops have also been reported in other studies. McGuire et al (1998) reported that excess precipitation and cooler temperatures reduced yields of winter legumes; Senthong and Pandey (1989) …”
Section: Resultsmentioning
confidence: 99%
“…Establishing a post-rice legume crop prior to or immediately after the rice harvest is crucial in maximizing the use of the entire residual soil water reservoir. Water deficits are likely during the late growth stages of a post-rice legume because of a receding water table (Senthong and Pandey, 1989;Timsina, 1989).…”
Section: Allowing Jbr Increased Nitrate Uptakementioning
confidence: 99%
“…Peanut is reported to withstand relatively larger soil water deficits than most grain legumes because of a higher root density in the lower soil depths (De Vries et al, 1989a;Senthong and Pandey, 1989).…”
Section: Allowing Jbr Increased Nitrate Uptakementioning
confidence: 99%